Avaliação de desempenho na perspectiva do balanced scorecard :um estudo da dimensão do aprendizado e crescimento nos restaurantes de Natal - Ferreira, Carlos José Wanderley (2006)
This work treats of a field research in restaurants of Natal. The principal objective of the research was to verify the companies they would be using some type of acting evaluation with base in no-financial perspectives, that if they assimilated to Balanced Scorecard proposal, in the dimension of the Learning and Growth. In the statistical treatment, the descriptive analysis was accomplished with part of the Descriptive Statistics. The crossed analysis was made with Cluster Analysis employment. It was reached the conclusion that would not be careful to affirm the exact percentile of the ones that they use them referred practices, because there is not an uniform use on the part of the establishments. It is admitted that, even in an informal way, intentionally or not, partly, the companies are been worth of some investigated methods. It is also concluded that the adoption of instruments of that nature can take the companies they advance her/it in competitiveness, strengthening to your continuity possibilities and of growth. The word-key of this healthy work Balanced Scorecard, Knowledge Organizacional, Evaluation of Acting, Strategy and Competitiveness